Harassment-induced changes in lion space use as a conflict mitigation tool - Petracca, LS; Frair, JL; Bastille-Rousseau, G; Macdonald, D; Loveridge, AJ (Wiley, 2021)
Human‐wildlife conflict represents a substantial threat to rural livelihoods and species persistence. Directed harassment (i.e., hazing) is one method for mitigating conflict, though gauging its effectiveness is often complicated by a lack of replication, controls, or effective contrasts. Herein we assessed whether African lions (Panthera leo) shifted their space use in response to a hazing program intended to deter lions from community lands adjacent to Hwange National Park, Zimbabwe. Using GPS‐collared lions (n = 16) from unique prides, we investigated the degree to which individuals exhibited (a) a large‐scale response by shifting their home ranges away from community lands, or (b) a fine‐scale response by increasingly avoiding areas near households post‐program initiation. Responses between “at‐risk” (those exposed to the program; n = 5) and “protected” (n = 11) lions varied, with at‐risk males shifting their home ranges to include 12.08% more national park and 9.04% less community lands post‐program (median), a shift not replicated by at‐risk females nor protected lions. However, the majority of at‐risk lions demonstrated increased attraction to households post‐program. We demonstrated that while aversive stimulus approaches may alter large‐scale space use by individual lions, constraints imposed by social structure and available habitat alternatives will affect the level of effort required to achieve program success.